Effects of TRX Training on Shoulder Strength Among Male Basketball Players - Chandrasekar, S J Albert (Journal of Neonatal Surgery, 2025)
The effects of eight weeks of TRX hanging training on male basketball players' shoulder strength were examined in this study. Fifteen young basketball players, ages 18 to 21, were randomly chosen as study participants from SRM IST, Chennai, in order to fulfill the study's objectives. The subjects underwent TRX training twice a week for 8 weeks. Shoulder strength was the dependent variables of the study. To determine whether there was a significant difference, the gathered data was statistically examined using the Paired T test. After eight weeks of TRX training, there was a substantial difference in the shoulder strength of male basketball players between their pre- and post-test results.